Mog1 knockout causes cardiac hypertrophy and heart failure by downregulating tbx5‐cryab‐hspb2 signalling in zebrafish. (22nd October 2020) - Gou, Dongzhi; Zhou, Juan; Song, Qixue; Wang, Zhijie; Bai, Xuemei; Zhang, Yidan; Zuo, Mengxia; Wang, Fan; Chen, Ailan; Yousaf, Muhammad; Yang, Zhongcheng; Peng, Huixing; et al.
Abstract: Aims: MOG1 is a small protein that can bind to small GTPase RAN and regulate transport of RNA and proteins between the cytoplasm and nucleus. However, the in vivo physiological role of mog1 in the heart needs to be fully defined. Methods: Mog1 knockout zebrafish was generated by TALEN. Echocardiography, histological analysis, and electrocardiograms were used to examine cardiac structure and function. RNA sequencing and real‐time RT‐PCR were used to elucidate the molecular mechanism and to analyse the gene expression. Isoproterenol was used to induce cardiac hypertrophy. Whole‐mount in situ hybridization was used to observe cardiac morphogenesis. Results: Mog1 knockout zebrafish developed cardiac hypertrophy and heart failure (enlarged pericardium, increased nppa and nppb expression and ventricular wall thickness, and reduced ejection fraction), which was aggravated by isoproterenol. RNAseq and KEGG pathway analyses revealed the effect of mog1 knockout on the pathways of cardiac hypertrophy, dilatation and contraction. Mechanistic studies revealed that mog1 knockout decreased expression of tbx5, which reduced expression of cryab and hspb2, resulting in cardiac hypertrophy and heart failure. Overexpression of cryab, hspb2 and tbx5 rescued the cardiac oedema phenotype of mog1 KO zebrafish. Telemetry electrocardiogram monitoring showed QRS and QTc prolongation and a reduced heart rate in mog1 knockout zebrafish, which was associated with reduced scn1b expression. Moreover, mog1 knockout resulted in abnormal cardiac looping during embryogenesis because of the reduced expression of nkx2.5, gata4 and hand2 . Conclusion: Our data identified an important molecular determinant for cardiac hypertrophy and heart failure, and rhythm maintenance of the heart.